Novasome: Combining Ufasome and Niosome for Excellent Vesicular Drug Delivery System (Sciences of Pharmacy, 2023)
Novasome technology is a novel encapsulation-based drug delivery method that is more effective and efficient than standard liposome systems. It is composed of a mixture of surfactant, cholesterol, and free fatty acids, which produce superior vesicle characteristics for drug delivery. Various studies have investigated the optimal combination of surfactant type, free fatty acid type, and their ratio, as well as the formulation factors that can significantly affect the vesicle characteristics. The novasome technology has demonstrated its potential for delivering a range of substances, including terconazole, fenticonazole, zolmitriptan, and vaccines. Novasomes can be produced using various methods, such as the thin film hydration (TFH) method, injection method, and vortex method combined with a suitable size reduction method. Future research can focus on exploring the potential of novasome technology for delivering a wider range of drugs and vaccines and developing more efficient and effective methods for producing novasome vesicles.